1996
DOI: 10.1111/j.1365-2672.1996.tb03548.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of technologically important traits in lactic acid bacteria isolated from spontaneous fermentations

Abstract: A set of 120 isolates of Lactohadus (75), Lactococcus (25) and Leuconostoc (20), mainly isolated from natural starter-free fermentation processes, has been screened for some technologically important traits, including lactose hydrolysis, extracellular polysaccharide production, fermentation of carbohydrates, antimicrobial agent susceptibility and bacteriocin production. Some of the strains exhibited important features for particular fermentations. Furthermore, the sensitivity resistance phenotype to antimicrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 15 publications
4
21
0
1
Order By: Relevance
“…faecalis isolates displayed resistance to up to 8 different antibiotics (oxacillin, spectinomycin, gentamicin, kanamycin, streptomycin, neomycin, clindamycin, and lincomycin) and variable resistance to furazolidone and tetracycline (data not shown). Similar results have also been observed in other studies with LAB (Herrero and others 1996; Danielsen and Wind 2003; Flórez and others 2005) and microstaphylococci (Gardini and others 2003; Perrin‐Guyomard and others 2005; Martín and others 2006) isolated from foods. This confirms that some bacterial resistance mechanisms are distributed among a wide variety of bacteria, whereas others appear to be more specific in certain species and genera of bacteria.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…faecalis isolates displayed resistance to up to 8 different antibiotics (oxacillin, spectinomycin, gentamicin, kanamycin, streptomycin, neomycin, clindamycin, and lincomycin) and variable resistance to furazolidone and tetracycline (data not shown). Similar results have also been observed in other studies with LAB (Herrero and others 1996; Danielsen and Wind 2003; Flórez and others 2005) and microstaphylococci (Gardini and others 2003; Perrin‐Guyomard and others 2005; Martín and others 2006) isolated from foods. This confirms that some bacterial resistance mechanisms are distributed among a wide variety of bacteria, whereas others appear to be more specific in certain species and genera of bacteria.…”
Section: Resultssupporting
confidence: 91%
“…Lactobacilli and leuconostocs may have a natural resistance to aminoglycosides, but low rates of resistance were observed in the lactobacilli and leuconostocs in the present study, whereas more variable rates of resistance were found in lactococci and enterococci (Table 2). Similar results were obtained by Herrero and others (1996) for LAB isolated from different Spanish cheeses (La Serena, Gamonedo, Cabrales, Majorero) and wines (Utiel‐Requena, Montilla‐Moriles). These researchers also found that lactococci were the most resistant to aminoglycosides (especially gentamicin), whereas leuconostocs were very susceptible to these antibiotics.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…This low lypolitic activity of LAB may represent an important advantage when they are used as starter cultures, as only a slight breaking of the milk fat during maturation is enough to induce aroma production without giving a rancid flavor in cheese [70]. Results from this study allow us to conclude that HALAB isolates E. faecium, L. pentosus, L. plantarum, W. thailandensis, T. halophilus, and L. farciminis could be selected to be included as adjunct starter cultures, since they fulfilled the customary requirements for cheesemaking.…”
Section: Discussionmentioning
confidence: 98%
“…bulgaricus (Masud et al, 1991). In modern production techniques, standardization, quality and safety of the product is considered to be of outstanding importance, therefore the mixtures of LAB strains are carefully selected to carry out the desirable fermentation processes (Herrero et al, 1996). The main technological properties of yoghurt bacteria during fermentation are acidification, texture enhancement and flavour production.…”
Section: Introductionmentioning
confidence: 99%